Analysis of the maternal factors associated with VLBW babies - Dr. Anand.K; Dr. Rabindran (Pediatric Review: International Journal of Pediatric Research, 2017)
Introduction: VLBW is associated with increased mortality and morbidity. In country like India where poverty, illiteracy & low socio-economic factors play a major role, incidence of VLBW & its complications can be reduced by targeting on the socio-demographic, obstetric factors, maternal nutrition & health education. Methodology: This is a Prospective study in a single centre over a period of 1 year. All newborns admitted to the neonatal unit during the study period with birth weight < 1500 gram were included and Still births & babies with major congenital malformations were excluded. An equal number of newborns with birth weight > 2500 gram were selected by simple randomized technique on same day of the selection of study group & were used as a control population to study maternal factors. Maternal factors analyzed in the study include Age of mother, Parity, Birth interval, Height, Weight, Mid arm circumference, Literacy level, Per capita income per month, Family structure, Mother’s occupation, Antenatal care, Bad obstetric history, Maternal disease during the antenatal period Neonatal details of birth weight, gestational age, sex of the baby was collected. Results: Higher incidence of VLBW babies were noted among young mothers, primiparity, when birth interval was < 2 years, maternal weight < 40kg and with MAC < 20 cm. Incidence of VLBW was more in mothers who were illiterate and with bad obstetric history. Conclusion: A well-nourished multiparous mother between 20-30 years with birth interval of > 2years with good literacy & without any BOH has the best chance of producing a good weight baby.